Language Assessment Literacy and the Professional Development of Pre-Service Language Teachers - Giraldo, Frank; Murcia Quintero, Daniel (Colombian Applied Linguistics Journal, 2019)
Language Assessment Literacy (LAL) research has focused on defining the knowledge, skills, and principles that the stakeholders involved in language assessment activities are required to master. However, there is scarce research on the relationship between LAL and the professional development of language teachers. Therefore, this exploratory action research study examined the impact of a language assessment course on pre-service teachers in a Colombian language teaching programme. Data were collected through questionnaires, interviews, teacher and researcher journals and class observations. The findings show that the course promoted theoretical, technical and operational dimensions in the language assessment design practices of the participants. In addition, it enhanced their LAL and professional development. Consequently, this study contends that the LAL course changed language assessment perceptions radically and encouraged pre-service teachers to design assessments conscientiously, a feature not explicitly stated in LAL research involving this group of stakeholders elsewhere.